Clinical Characteristics of Pediatric Cases of COVID-19 in Hunan, China: A Retrospective, Multi-Center Case Series - Wu, Lei; Zhang, Xiao-Fo; Yang, Yong; Yi, Xiu-Ying; Jiang, Xin-Ping; Han, Hai-Ying; Cao, Xiao-Ying; Wang, Tuan-Mei; Wang, Man-Zhi (Frontiers in Pediatrics, 2021)
Objective Aimed to investigate the epidemiological characteristics, clinical features, treatment, and short-term prognosis of SARS-CoV-2 infection in children. Methods A retrospective analysis was conducted in 48 children with SARS-CoV-2 admitted to 12 hospitals in eight cities in Hunan province, China, from January 26, 2020 to June 30, 2020. Results Of the 48 cases, 16 (33%) were imported from other provinces. There were 11 (23%) asymptomatic cases. In children with symptoms, 15 cases (31%) were mild, 20 cases (42%) were moderate, and 2 cases (4%) were severe. The most common symptom was fever (n = 20, 42%). Other symptoms included cough (n = 19, 40%), fatigue (n = 8, 17%), and diarrhea (n = 5, 10%). In the early stage, the total peripheral blood leukocytes count decreased in one case (2%) and increased in three cases (6%); the lymphocytes count decreased in five cases (10%). C-reactive protein was elevated in three cases (6%), and procalcitonin was increased in two cases (4%). There were abnormal chest CT changes in 22 children (46%), including 15 (68%) with patchy ground glass opacity, 5 (22%) with consolidation, and 2 (10%) with mixed shadowing. Of the 22, 12 cases (55%) had one-lobe involvement; in the other 10 cases (45%), two or more lobes were involved. In addition to supportive treatment, antiviral therapy was received by 41 children (85%), 11 patients (23%) were treated with antibiotics, and 2 (4%) were treated with methylprednisolone and intravenous immunoglobulin. Conclusions Most cases of SARS-CoV-2 infection in children in Hunan province were asymptomatic, mild, or moderate. Close family contact was the main route of infection. It appeared that the younger the patient, the less obvious their symptoms. Epidemiological history, nucleic acid test, and chest imaging were important tools for diagnosis in children.